Influence of Socio-Demographic, Occupational and Lifestyle Variables on Sleep Time - Dutheil F; Saint-Arroman C; Clinchamps M; Flaudias V; Fantini ML; Pereira B; Berthon M; Laporte C; Baker JS; Charkhabi M; Cocco P; Lecca R; et al. (Nature and Science of Sleep)
Frederic Dutheil,1,* Chloé Saint-Arroman,1,* Maëlys Clinchamps,1 Valentin Flaudias,2 Maria Livia Fantini,3 Bruno Pereira,4 Mickael Berthon,5 Catherine Laporte,6 Julien Steven Baker,7 Morteza Charkhabi,8 Pierluigi Cocco,9 Rosamaria Lecca,9 Monica Puligheddu,9 Michela Figorilli,9 Marek Zak,10 Ukadike Chris Ugbolue,11 Esther Ubago-Guisado,12 Luis Gracia-Marco,13 Jean-Baptiste Bouillon-Minois,1 Luc Vialatte14 1Université Clermont Auvergne, CNRS, Physiological and Psychosocial Stress, LaPSCo, Preventive and Occupational Medicine, University Hospital of Clermont-Ferrand, Clermont-Ferrand, F-63000, France; 2Department of Psychiatry, University Hospital of Clermont-Ferrand, University of Clermont Auvergne, Clermont-Ferrand, France; 3NPsy-Sydo, Neurology Department, University Hospital of Clermont-Ferrand, Université Clermont Auvergne, Clermont-Ferrand, France; 4Biostatistics Department, University Hospital of Clermont-Ferrand, Clermont-Ferrand, France; 5Laboratoire de Psychologie Sociale et Cognitive (LAPSCO), Université Clermont Auvergne, CNRS, Clermont-Ferrand, France; 6Clermont Auvergne INP, University Hospital of Clermont-Ferrand, CNRS, Institut Pascal, Université Clermont Auvergne, Clermont-Ferrand, F-63000, France; 7Department of Sport, Physical Education and Health, Centre for Health and Exercise Science Research, Hong Kong Baptist University, Kowloon Tong, Hong Kong; 8Université Clermont Auvergne, CNRS, Physiological and Psychosocial Stress, LaPSCo, Clermont-Ferrand, France; 9Department of Medical Sciences and Public Health, Neurology Unit, University of Cagliari and AOU Cagliari, Monserrato, Cagliari, 09042, Italy; 10Collegium Medicum, Institute of Health Sciences, Jan Kochanowski University of Kielce, Kielce, Poland; 11School of Health and Life Sciences, Institute for Clinical Exercise & Health Science, University of the West of Scotland, Glasgow, UK; 12Epidemiology and Control of Chronic Diseases, CIBER of Epidemiology and Public Health (CIBERESP), Madrid, 28029, Spain; 13Epidemiology, Prevention and Cancer Control, Instituto de Investigación Biosanitaria Ibs. Granada, Granada, 18012, Spain; 14Preventive and Occupational Medicine, University Hospital of Clermont-Ferrand, AIST – La prevention Active, University of Clermont Auvergne, Clermont-Ferrand, France*These authors contributed equally to this workCorrespondence: Frederic Dutheil, Email frederic.dutheil@uca.frBackground: Socio-demographic, occupational and lifestyle variables influence total sleep time. Therefore, we aimed to evaluate the influence of those variables on sleep time, and to study risk factors of being a short sleeper.Methods: The COVISTRESS international study is an online questionnaire using the secure REDCap® software. Total sleep time was evaluated using declared bedtime and time of awakening and was analyzed as a quantitative variable and as a qualitative variable.Results: We included 549 respondents to the questionnaire, divided into 10-year age groups ranging from < 30yo to ≥ 60yo. The mean quantity of sleep was 7.11± 1.43 hours per night. Factors that reduce total sleep time were age (coefficient − 0.19, 95CI − 0.33 to 0.06), being an employee (− 0.46, − 0.85 to − 0.06), working time (− 0.18, − 0.31 to 0.05), smoking ≥ 5 cigarettes/day (− 0.5, − 0.95 to − 0.20), high stress at work (− 0.64, − 0.96 to − 0.32) and at home (− 0.66, − 0.97 to − 0.35). Being a student (0.61, 0.02 to 1.19), working less than 25h per week (0.57, 0.17 to 0.97) and telework (0.46, 0.02 to 0.89) increased total sleep time. The risk factors of being a short sleeper were age (odds ratio 1.27, 95CI 1.07 to 1.51), being an employee (2.58, 1.36 to 4.89), smoking ≥ 5 cigarettes/day (2.73, 1.54 to 4.84) and a high level of stress at work (2.64, 1.45 to 4.82) and at home (3.89, 2.25 to 6.63). Physical activity ≥ 2.5 hours/week tended to decrease the risk of being a short sleeper by 35%.Conclusion: We demonstrated the concomitant impact of sociodemographic, occupational and lifestyle behavior on sleep, which may help to build efficient preventive strategy.Keywords: total sleep time, sociodemographic variables, occupational variables, mental health